2016
DOI: 10.1177/1467358415610371
|View full text |Cite
|
Sign up to set email alerts
|

The role of travel experience in the structural relationships among tourists’ perceived image, satisfaction, and behavioral intentions

Abstract: The theoretical relationships among tourists’ perceived destination image, satisfaction, and future behavioral intentions are very important for the tourism industry and have been studied by many scholars. This paper examines how these relationships differ for tourists with different travel experiences by studying 514 Mainland Chinese outbound travelers to Macau. The conceptual model incorporates the exogenous formative concept of perceived image and the endogenous reflective concept of visitor satisfaction as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 36 publications
1
32
0
1
Order By: Relevance
“…revealed that E-WOM is one of the factors influencing destination image. Liu, Li, & Kim (2017) mentioned that destination images can influence tourist behavioral intentions in two ways. According to perceived service quality, attractiveness, comfort, value for money, and exotic atmosphere are factors that affect the affective image of a country.…”
Section: Destination Imagementioning
confidence: 99%
“…revealed that E-WOM is one of the factors influencing destination image. Liu, Li, & Kim (2017) mentioned that destination images can influence tourist behavioral intentions in two ways. According to perceived service quality, attractiveness, comfort, value for money, and exotic atmosphere are factors that affect the affective image of a country.…”
Section: Destination Imagementioning
confidence: 99%
“…Dolayısıyla müşteri memnuniyeti hizmet satın alımından önce başlayıp, satın alma sonrasına kadar devam etmektedir (Ciavolino ve Dahlgaard, 2007). Müşteri satın aldığı hizmet performansı beklentilerinin üzerinde gerçekleşmişse memnun olmaktadır (Liu, Li, ve Kim, 2017;Ryu ve Han, 2010). Eğer müşteri beklentileri karşılanırsa, müşterinin hem duyusal hem de bilişsel memnuniyet artacaktır.…”
Section: Müşteri Memnuniyetiunclassified
“…The attributes considered relevant for this study were selected according to the attractions and nature of destination, its positioning, and on the objectives of the assessment of perceived image in online environment, based on a wide range of variables collected from the literature [4], [5], [8], [9], [15], [16], [17]. These particularities of the destination will also determine whether specific or more general attributes are chosen.…”
Section: A Destination Image Measurement and Formationmentioning
confidence: 99%
“…The destination image contributes significantly to understand how people evaluate and act towards destinations, and consequently to develop the potential pull of a destination besides contributing to increase the satisfaction of the experience and desire to visit the destination in real. [3], [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%